Baseline assessment of the rodent species composition in the cultivated areas in Leyte Sab-a Basin Peatland, Estern Visayas, Philippines - Dumas, Mikaella Lizette T. (2023)
The Philippines is home to the most distinctive and highly diverse mammalian assemblage worldwide, with a recorded total of 167 species, of which 60% are endemic to the Philippines. Among the terrestrial mammals, one-third comprises Murid rodents which constitute 60 native species and seven non-native rodents. Due to their rampant infestation, philippine rodents are depicted primarily as pests in both rural and urban settings. Unbeknownst to many that Philippine rodents are mainly native rodents that are proven to be non-invasive and beneficial in crop cultivation; native rodents often suffer as non-target species of pest control efforts, which consequently pose threats to the diverse pool of native rodent species in the country. The same high rate of endemism and species diversity can be observed in peatlands such as the Leyte Sab-a Basin Peatland (LSBP), which is one of the two major peatlands in the Philippines. Unfortunately, this biodiversity hotspot has been subjected to various land-use conversions. The present assessment confirmed the presence of two non-native rodents (i.e., Rattus tanezumi and R. norvegicus) in the cultivated areas of LSBP. R. tanezumi tend to be closely associated with human dwellings and coconut trees, while R. norvegicus were more common within croplands away from the villages. Moreover, the morphometric analysis of the external body measurements of the trapped rodents reveals no notable sexual dimorphism indicating that the environmental conditions in LSBP are shared by both sexes of the species. Furthermore, results indicate low rodent species diversity and heavily disturbed conditions of LSBP. Considering the high endemism in peatlands, it is not unlikely for native rodent species to occur in LSBP, only if conditions improve and become favorable for them.